Development and evaluation of a cloud bookcase system for mobile library. Issue 2 (5th June 2020) - Lai, Chin-Feng; Zhong, Hua-Xu; Chiu, Po-Sheng; Pu, Ying-Hung
Abstract : Purpose: This study aims to adopt cloud technology and develop a "cloud bookcase system" to make it possible to provide consistent mobile reading experiences to allow readers to use all kinds of mobile devices to read e-books. Design/methodology/approach: This study implements a cloud bookcase and uses four indicators (system quality, information quality, service quality, user satisfaction) to evaluate the system for reading e-books. Findings: After completing the system, the authors used a questionnaire to evaluate the system. The results show that the quality can meet the needs and satisfaction of users. Subsequent interviews with some of the participants also reveal the biggest concerns of readers include library policy, resources and system quality. Practical implications: System quality, information quality, service quality and satisfaction are adopted as the indicators to assess the ratings from people using mobile devices to read e-books on the cloud bookcase system developed in this study to evaluate whether the cloud bookcase system is a successful information system as well as the relations between mobile device factors and user ratings. The results indicate that the ratings from more than half of the readers for the system, as shown in the various indicators, achieve more than 60%. From the interview results, the results show that some participants also reveal there is still room for improvement in some areas. Originality/value: This study implements a cloud bookcase and there are three contributions: (1) the cloud bookcase system developed in this study based on related theories proves able to meet the needs of users, (2) this system had high ratings for all four indicators, (3) the interview responses reveal that most people regard system quality as the most important, and some of the people value some of the items more, including library policy, readers' interests and more resources, especially the number of e-books available.